Variability of M. phaseolina Sesame isolates obtained from different geographical region: Variability of M. phaseolina Sesame isolates obtained from different geographical region - SHIVANI NAGPURE; K N GUPTA; AKSHAY SALBARDE (Journal of Oilseeds Research, 2023)
The cultural characteristics of the three isolates were studied, the cultural characters of the isolates colony growth, colony texture, colony colour type studied. Into which all the isolates show variability into the characters of the isolates. In case of colony colour isolate Mp 1 (Jabalpur, M.P.) and Isolate Mp 2 (Mandor, R.J.) show grey coloured colony was observed but isolate Mp 3 (Vridhachalam, T.N.) show dark black colour colony. In case of colony texture two type of colony texture was seen, Appressed and fluffy growth and suppressed and dense growth. In case of Mp 1 (Jabalpur) and Mp 2 (Mandor) isolate , appressed and fluffy growth types of growth was observed while in case of isolate Mp 3 (Vridhachalam) suppressed and dense growth was seen. All the isolates of M. phaseolina do not show any kind of significant difference in colony growth. Maximum radial growth (90.00 mm) was observed in all three isolates of M. phaseolina.